KEPUASAN WISATAWAN DI OBYEK WISATA ALAM CURUG SEWU KABUPATEN KENDAL - , PROBO SUSANTO, Kaharuddin, S.Hut., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
One of the tourism areas which already implemented a nature tourism activity and became a tourist affinity was Curug Sewu Nature Tourism Object, Kendal Regency, Central Java. The descent of the tourism amount in Curug Sewu Nature Tourism Object indicated the descent of service/performance management quality in this tourism object. The aims of this study are (1) to determine institutional developing of tourism management at Curug Sewu Nature Tourism Object, (2) to identify the satisfaction of the tourist at Curug Sewu Nature Tourism Object. This study was analyzed using two kind of methods (1) Institutional Development Framework (IDF) Analysis to determine the development, (2) Customer Satisfaction Index (CSI) to identify the satisfaction rates. The compatibility rates were seen from the result of customer satisfaction index, to identify the compatibility rates of tourist expetation and management work at Curug Sewu Nature Tourism Object. The result was also analyzed using Importance Performance Analysis (IPA) to determine management strategy. The result showed that institutional development level of tourist management were the steady stage with IDF point was 2.92. The level of tourist satisfaction was 0.5693 which means the tourist who visited Curug Sewu Nature Tourism Object generally pleased enough by the management attribute.